Towards the Development of a Protocol for Cryopreservation of Embryos of Rambutan (Nephelium Lappaceum L.) - Hiew, Yee Hooi (1991)
Long term storage of recalcitrant seeds by conventional storage methods thus far have been unsuccessful. In this study, the excised embryos from seeds of Rambutan (Nephelium lappaceum), a recalcitrant tropical fruit species has been at tempted for long term storage through cryopre. Stage of fruit maturity was found to be one of the important factor for the survival of embryos in vitro. The embryos excised from mature unripe fruits were selected as the most appropriate for use in this study.